Recent advances of cerium oxide nanoparticles in synthesis, luminescence and biomedical studies： a review - 何立莹 苏玉民 蒋兰宏 石士考 (Journal of rare earths, 2015)
Nanostructured cerium oxide （CeO2） commonly known as nanoceria is a rare earth metal oxide, which plays a technologically important role due to its versatile applications as antomobile exhaust catalysts, oxide ion conductors in solid oxide fuel cells, electrode materials for gas sensors, ultraviolet absorbents and glass-polishing materials. However, nanoceria has little or weak luminescence, and therefore its uses in high-performance luminescent devices and biomedical areas are limited. In this review, we present the recent advances of nanoceria in the aspects of synthesis, luminescence and biomedical studies. The CeO2 nanoparticles can bc synthesized by solution-based methods including co-precipitation, hydrothemlal, microemulsion process, sol-gel techniques, combustion reaction and so on. Achieving controlled morphologies and enhanced luminescence efficiency of nanoceria particles arc quite essential for its potential energyand environment-related applications. Additionally, a new fiontier for nanoccria particles in biomedical research has also been opened, which involves low toxicity, retinopathy, biosensors and cancer therapy aspects. Finally, the summary and outlook on the challenges and perspectives of the nanoceria particles are proposed.